Density and distribution mapping of invasive plant Jatropha gossypiifolia in priority savanna of Bama Resort, Baluran National Park, East Java, Indonesia - Solfiyeni Solfiyeni; Adinda Nurmalasari (Society for Indonesian Biodiversity, 2025)
Abstract. Solfiyeni, Nurmalasari A. 2025. Density and distribution mapping of invasive plant Jatropha gossypiifolia in priority savanna of Bama Resort, Baluran National Park, East Java, Indonesia. Biodiversitas 26: 255-264. Jatropha gossypiifolia (Bellyache bush) is one of the invasive alien plant species in the savanna of Baluran National Park, East Java, Indonesia. The invasiveness of J. gossypiifolia is the main focus of this study because this species has the potential to have a significant and far-reaching impact on the stability of the savanna ecosystem in Baluran National Park. This study aims to determine the density, distribution pattern, and distribution area of J. gossypiifolia and to analyze environmental factors that affect its presence in the savanna of Bama Resort, Baluran National Park. The survey method for distribution mapping and a single plot method to determine density and distribution pattern. Meanwhile, to analyze the relationship between environmental factors and plant density of J. gossypiifolia, Canonical Component Analysis (CCA) was used. The results showed that the density of J. gossypiifolia plants in the observation area of 400 m2 was 1.94 individuals/m2 or estimated in hectares around 19,400 individuals/ha and this plant was found growing in 15 sub-plots out of a total of 16 sub-plots observed in the field. The distribution pattern of J. gossypiifolia plants in the observation area is clustered with a Morisita Index value of 1.48. Furthermore, it is known that the distribution area of J. gossypiifolia plants in the priority savanna of Bama Resort is around 25 hectares of the total savanna area of Bama Resort of around 512 hectares. The existence of J. gossypiifolia plants is strongly influenced by the high and low light intensity. Jatropha gossypiifolia plants have spread quite widely in the priority savanna of Bama Resort, Baluran National Park. This plant is most commonly found growing in savannas close to the road, so it is necessary to routinely monitor each savanna as an effort to manage invasive alien plants in the savannas of Baluran National Park.